The Season Calendar System of Gorontalo Society: Socio-Cultural Analysis Based on Local Wisdom and Appropriate Technology - Tamu, Yowan; Dako, Amirudin (KOMUNITAS: International Journal of Indonesian Society and Culture, 2018)
Gorontalo society is well-known to have a great combination between traditional and cultural nuances. One of the undeniable phenomena is the habit of doing activities and transactions at particular times. This phenomenon then creates several terms such as wedding season, planting season and Hajatan season where those certain custom rituals are only performed in Gorontalo region. The process of inventory of this phenomenon becomes an important step that should be done to ensure that the values contained in the local wisdom of the people of Gorontalo can be documented and become written legacy for future generations. By applying a social research method, this preliminary study aims at creating an inventory for the ongoing local wisdoms in Gorontalo, especially dealing with the creation of a written document containing their season calendar. The draft of season calendar document that had been produced, in the next stage, was then analyzed. Later stage was to create a computer application to be developed in the form of information system prototype containing local calendar module based on local wisdom of Gorontalo society. The application should be easily accessible by local, national and global community, enriched with spatial data presentations and serving as a support for documentation and digital publications. The study is expected to be an effort to preserve local wisdom of Gorontalo as well as become the part of modern culture and knowledge.